WC-based ceramic self-lubricating layer filling method under extreme pressure driving
By adding hard hard sintering materials to WC-based ceramics and forming pore ceramics using extreme pressure, and then filling the lubricating layer with extreme temperature and punch load, the problem of degradation of mechanical properties under extreme cutting conditions is solved, and synergistic efficiency of mechanical and lubricating performance is achieved.
Patent Information
- Application Number
- CN202411968138.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-30
- Publication Date
- 2025-04-08
- Estimated Expiration
- 2044-12-30
AI Technical Summary
The mechanical properties of existing WC-based ceramic self-lubricating materials have decreased under extreme cutting conditions, making it difficult to achieve synergistic efficiency of mechanical and lubricating properties.
Using extreme pressure-driven method, by mixing CBN or diamond powder with WC polycrystalline powder, sintering at high temperature and high pressure to form pore ceramics, and extruding the self-lubricating powder into the micropores in the ceramic using extreme temperature load to form a lubricating layer.
It significantly improves the mechanical properties and wear resistance of WC-based ceramics, achieves synergistic efficiency of mechanical and lubricating properties, and the filling of the lubricating layer does not affect the hardness and toughness of the ceramics.
Smart Images

Figure CN119775011A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of inorganic non-metallic material preparation, and more particularly to a WC-based ceramic self-lubricating layer filling method driven by extreme pressure. Background Art
[0002] High-speed cutting is an important way to promote the rapid upgrading of the manufacturing industry. However, as the cutting speed increases, the area covered by the cutting fluid decreases, and the extreme thermal load formed places stringent requirements on the performance of the tool material. WC-based self-lubricating ceramic tools can autonomously form a lubricating film during the cutting process, effectively improving the cutting conditions, but because the ceramic lubricating component is relatively "soft", the mechanical properties are significantly reduced. Regulating the content, particle size and distribution of ceramic lubricating components is the main way to shorten the gap between the mechanical properties of self-lubricating ceramics and traditional ceramics. However, when the matrix and lubricating particles are sintered together, the lubricating particles, as "impurities", will hinder the bonding between the atoms of the matrix and form pores, which will inevitably lead to a decrease in mechanical properties. How to eliminate the influence of lubricating components on the mechanical properties of ceramics and achieve synergistic enhancement of mechanical-lubricating properties is an urgent problem to be solved.
[0003] Studies have shown that the preparation of self-lubricating ceramic materials with excellent wear resistance requires the materials to have high hardness, high toughness, high density, and good high-temperature stability, which poses great engineering challenges.
[0004] Therefore, how to develop a WC-based ceramic self-lubricating layer filling method driven by extreme pressure is an urgent problem that technicians in this field need to solve. Summary of the invention
[0005] In view of this, the present invention provides a WC-based ceramic self-lubricating layer filling method driven by extreme pressure.
[0006] In order to achieve the above object, the present invention adopts the following technical solution:
[0007] A WC-based ceramic self-lubricating layer filling method driven by extreme pressure comprises the following steps:
[0008] (1) CBN or diamond powder and WC polycrystalline powder are uniformly mixed in a volume ratio of (1-3):(7-9) to obtain a mixed powder, the mixed powder is pre-pressed into a shape, and then wrapped with a metal inclusion;
[0009] (2) sintering the mixed powder in the metal package at high temperature and high pressure, the specific steps are: first increasing the pressure to a set pressure, then increasing the temperature, maintaining the temperature, and then slowly cooling to room temperature, and finally continuing to maintain the pressure for a period of time and then slowly reducing the pressure;
[0010] (3) taking out the sample sintered in step (2), removing the metal inclusions outside the sample, obtaining a WC-based porous ceramic, and then processing it into a specified shape;
[0011] (4) coating the processed WC-based porous ceramic with a layer of self-lubricating powder, and then coating it with a metal inclusion;
[0012] The self-lubricating powder is a metal powder, and the metal inclusion is treated at high temperature and high pressure. The specific steps are: first increase the pressure to a set pressure, then increase the temperature to the melting point of the metal powder under the set pressure, keep the temperature, stop heating, continue to keep the pressure for a period of time, and then slowly reduce the pressure;
[0013] Alternatively, the self-lubricating powder is a non-metallic powder, and the metal inclusion is treated under high pressure, specifically, the steps are: firstly increasing the pressure to a set pressure, maintaining the pressure for a period of time, and then slowly reducing the pressure;
[0014] (5) Taking out the sample after being processed in step (4), removing the metal inclusions and residual self-lubricating blocks outside the sample, and obtaining a WC-based self-lubricating ceramic including a lubricating layer.
[0015] Furthermore, in step (1), the grain size of the CBN or diamond powder is 0.2 to 50 μm, and the grain size of the WC powder is 0.2 to 10 μm.
[0016] Furthermore, in step (2) and step (4), the pressure is set to 5.5 GPa.
[0017] Furthermore, in step (1), the self-lubricating powder is MoS2, WS2, Cu or Al powder, and the particle size of the self-lubricating powder is 10nm-10μm.
[0018] Furthermore, in step (1), the pre-pressing pressure is 0.1 GPa and the holding time is 1 s.
[0019] Furthermore, in step (2), the pressure increase rate and the pressure reduction rate are 5 GPa / min, the temperature is increased to 300-1800°C, the temperature increase rate is 100°C / min, the holding time is 2-50 minutes, the temperature reduction rate is 10°C / min, the pressure is maintained for 5 minutes and then the pressure is slowly reduced to 0 GPa.
[0020] Furthermore, the metal inclusions in step (2) and step (4) are Mo, Zr or Ta.
[0021] Furthermore, in step (4), the layer thickness of the self-lubricating powder is 0.5 mm or more.
[0022] Further, in step (4), the self-lubricating powder is a metal powder, and is treated at high temperature and high pressure, with a pressure increase rate and a pressure reduction rate of 5 GPa / min, and the temperature is increased to the melting point of the metal powder at 5.5 GPa, the temperature increase rate is 100°C / min, the holding time is 5 minutes, the heating is stopped, the pressure is maintained for 5 minutes, and then the pressure is slowly reduced to 0 GPa;
[0023] Alternatively, the self-lubricating powder is a non-metallic powder, and is subjected to high pressure treatment, with a pressure increase rate and a pressure reduction rate of 5 GPa / min, and the pressure is maintained for 5 minutes and then slowly reduced to 0 GPa.
[0024] Beneficial effects of the present invention: The present invention adds a hard and difficult-to-sinter material as a second phase into a WC matrix, thereby improving the mechanical properties of WC ceramics and forming interconnected pores between WC ceramic grains to prepare porous ceramics; using extreme temperature and pressure loads, solid / liquid self-lubricating particles are filled into the micropores in the ceramic along the ceramic pores, and the particle size of the self-lubricating particles can be much larger than the pore size of the micropores in the ceramic.
[0025] The present invention processes ceramic sintering and lubricating phase filling in steps, first synthesizing a ceramic matrix with natural pores, and then using extreme pressure to "squeeze" lubricating particles into the ceramic pores. This not only completely solves the problem of mechanical property degradation caused by lubricating particles, but also further enhances the mechanical properties of the ceramic, achieving synergistic enhancement of mechanical and lubricating properties.
[0026] Adding CBN particles / diamond as the second phase in the WC matrix improves the hardness and toughness of the WC ceramics, and forms interconnected micropores between the WC ceramic grains to prepare microporous ceramics;
[0027] The lubricating particles are wrapped around the sintered WC-based microporous ceramics, and the lubricating particles are squeezed into the ceramics using extreme temperature and pressure loads to form a lubricating layer, which gives the WC-based ceramics self-lubricating properties.
[0028] The mechanical properties of the WC-based self-lubricating ceramics prepared by the method of the present invention are the same as those of the non-lubricating ceramics;
[0029] The wear resistance of the WC-based self-lubricating ceramic prepared by the method of the present invention is significantly improved compared with the non-lubricating layer. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 It is a process flow chart of the present invention;
[0031] Figure 2 This is a scanning electron microscope analysis image of the WC-CBN-MoS2 self-lubricating ceramic of Example 1;
[0032] Figure 3 This is the SEM analysis of WC-CBN-Cu self-lubricating ceramics in Example 2
[0033] Figure 4 This is a scanning electron microscope analysis image of the WC-CBN-WS2 self-lubricating ceramic of Example 3;
[0034] Figure 5 This is the scanning electron microscope analysis image of the comparative example 1 WC-CBN-MoS2 self-lubricating ceramic. DETAILED DESCRIPTION
[0035] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0036] Example 1
[0037] The WC-based ceramic self-lubricating layer filling method driven by extreme pressure comprises the following steps:
[0038] (1) CBN powder with a grain size of 5-10 μm and WC powder with a grain size of 200 nm are uniformly mixed in a volume ratio of 1:4 to obtain a mixed powder, and the mixed powder is pre-pressed; the pre-pressing pressure is 0.1 GPa, and the holding time is 1 s; a molded sample is obtained, and the molded sample is wrapped with a Mo metal inclusion;
[0039] (2) The molded sample with the metal inclusions is loaded into a high-pressure sintering unit, and then sintered at high temperature and high pressure. The specific steps are: first increase the pressure to a set pressure of 5.5 GPa at a pressure increase rate of 5 GPa / min, then increase the temperature to 1350°C at a temperature increase rate of 100°C / min, keep the temperature for 10 minutes, cool to room temperature at a temperature decrease rate of 10°C / min, continue to maintain the pressure for 5 minutes, and then slowly reduce the pressure to 0 GPa at a pressure decrease rate of 5 GPa / min;
[0040] (3) taking out the sample after high temperature and high pressure sintering in step (2), removing the metal Mo inclusion wrapped around the outside of the sample, obtaining a WC-CBN-based porous ceramic, and then processing it into a cylindrical shape with a height of 3 mm and a diameter of 10 mm;
[0041] (4) Wrapping the processed WC-CBN-based porous ceramic with a layer of self-lubricating powder MoS2 powder, the particle size of the self-lubricating powder is 1 μm, the layer thickness of the self-lubricating powder is 1 mm, and then wrapping it with a metal inclusion, the material of the metal inclusion is Mo, and placing the sample with the metal inclusion into a high-pressure unit, and then high-pressure treatment, the specific steps are: first increase the pressure to a set pressure of 5.5 GPa, the pressure increase rate is 5 GPa / min, and then slowly reduce the pressure to 0 GPa after maintaining the pressure for 5 minutes, and the pressure reduction rate is 5 GPa / min;
[0042] (5) Taking out the sample after high pressure treatment in step (4), removing the metal inclusions and residual self-lubricating blocks wrapped around the outside of the sample, and obtaining WC-CBN-MoS2 ceramics containing a lubricating layer.
[0043] The thickness of the ceramic lubricating layer was 1.5 μm. The Vickers hardness of the WC-CBN microporous ceramic was measured to be 33.5 ± 1.1 GPa and the fracture toughness was 9.95 ± 0.5 MPa.m. 1 / 2 ; The nanoindentation hardness of the WC-CBN-MoS2 ceramic lubrication layer is 34.5±1.2GPa and the fracture toughness is 10.05±0.6MPa.m 1 / 2 The hardness and toughness of WC-based ceramics remain unchanged before and after the lubricating layer is filled.
[0044] The wear resistance of WC-CBN microporous ceramics and WC-CBN-MoS2 ceramics was measured by rubbing against a cemented carbide ball (YG6) (pressure 10N, friction time 15min, rotation speed 400rpm). The wear rate of WC-CBN microporous ceramics was 150×10 -6 mm 3 / Nm, the wear rate of WC-CBN-MoS2 is 20×10 -6 mm 3 / Nm, the wear resistance of WC-based ceramics after high-pressure filling of the lubricating layer is significantly improved compared with that before filling.
[0045] Example 2
[0046] The WC-based ceramic self-lubricating layer filling method driven by extreme pressure comprises the following steps:
[0047] (1) Diamond powder with a grain size of 5-10 μm and WC powder with a grain size of 200 nm are uniformly mixed in a volume ratio of 1:4 to obtain a mixed powder; the mixed powder is pre-pressed into a mold using a pressure of 0.1 GPa with a holding time of 1 s, and the molded sample is wrapped with a Zr metal inclusion.
[0048] (2) The molded sample with the metal inclusions is loaded into a high-pressure sintering unit, and then sintered at high temperature and high pressure. The specific steps are: first increase the pressure to a set pressure of 5.5 GPa at a pressure increase rate of 5 GPa / min, then increase the temperature to 1400°C at a heating rate of 100°C / min, keep the temperature for 30 minutes, cool to room temperature at a cooling rate of 10°C / min, continue to maintain the pressure for 5 minutes, and then slowly reduce the pressure to 0 GPa at a pressure reduction rate of 5 GPa / min;
[0049] (3) taking out the sample after high temperature and high pressure sintering in step (2), removing the Zr metal inclusions wrapped around the outside of the sample, obtaining WC-diamond microporous ceramics, and then processing them into a cylindrical shape with a height of 3 mm and a diameter of 10 mm;
[0050] (4) Wrapping the processed WC-based porous ceramic with a layer of self-lubricating powder Cu powder, the particle size of the self-lubricating powder is 10 μm, the layer thickness of the self-lubricating powder is 2 mm, and then wrapping it with a metal inclusion, the metal inclusion is Zr, and the raw material with the metal inclusion is loaded into a high-pressure sintering unit, and then treated with high temperature and high pressure, the specific steps are: first increase the pressure to a set pressure of 5.5 GPa, the pressure increase rate is 5 GPa / min, then increase the temperature to 1400°C, the melting point of Cu at 5.5 GPa, the heating rate is 100°C / min, keep warm, the heat preservation time is 5 minutes, stop heating, continue to hold the pressure for 5 minutes, and then slowly reduce the pressure to 0 GPa, the pressure reduction rate is 5 GPa / min;
[0051] (5) Taking out the sample after the high temperature and high pressure treatment in step (4), removing the metal inclusions and residual self-lubricating blocks wrapped around the outside of the sample, and obtaining a WC-diamond-Cu ceramic containing a lubricating layer.
[0052] The thickness of the ceramic lubricating layer was 10 μm. The Vickers hardness of the WC-diamond microporous ceramic was measured to be 28.3±1.3 GPa and the fracture toughness was 8.45±0.5 MPa.m. 1 / 2 ; The nanoindentation hardness of the WC-diamond-Cu ceramic lubrication layer was measured to be 27.5±1.1GPa and the fracture toughness was 8.05±0.4MPa.m 1 / 2 The hardness and toughness of WC-based ceramics remain unchanged before and after the lubricating layer is filled.
[0053] The wear resistance of WC-diamond microporous ceramics and WC-diamond-Cu was measured by rubbing against a cemented carbide ball (YG6) (pressure 10N, friction time 15min, rotation speed 400rpm). The wear rate of WC-diamond microporous ceramics was 180×10 -6 mm 3 / Nm, the wear rate of WC-diamond-Cu is 80×10 -6 mm 3 / Nm, the wear resistance of WC-based ceramics after high-pressure filling of the lubricating layer is significantly improved compared with that before filling.
[0054] Example 3
[0055] The WC-based ceramic self-lubricating layer filling method driven by extreme pressure comprises the following steps:
[0056] (1) CBN powder with a grain size of 5-10 μm and WC powder with a grain size of 200 nm are uniformly mixed in a volume ratio of 1:4 to obtain a mixed powder, and the mixed powder is pre-pressed; the pre-pressing pressure is 0.1 GPa, and the holding time is 1 s; a molded sample is obtained, and the molded sample is wrapped with a Mo metal inclusion;
[0057] (2) The molded sample with the metal inclusions is loaded into a high-pressure sintering unit, and then sintered at high temperature and high pressure. The specific steps are: first increase the pressure to a set pressure of 5.5 GPa at a pressure increase rate of 5 GPa / min, then increase the temperature to 1450°C at a temperature increase rate of 100°C / min, keep the temperature for 10 minutes, cool to room temperature at a temperature decrease rate of 10°C / min, continue to keep the pressure for 5 minutes, and then slowly reduce the pressure to 0 GPa at a pressure decrease rate of 5 GPa / min;
[0058] (3) taking out the sample after high temperature and high pressure sintering in step (2), removing the metal Ta inclusion wrapped around the outside of the sample, obtaining a WC-CBN-based porous ceramic, and then processing it into a cylindrical shape with a height of 3 mm and a diameter of 10 mm;
[0059] (4) Wrapping the processed WC-based porous ceramic with a layer of self-lubricating powder WS2 powder, the particle size of the self-lubricating powder is 1 μm, the layer thickness of the self-lubricating powder is 1 mm, and then wrapping it with a metal inclusion, the material of the metal inclusion is Mo, and the sample with the metal inclusion is placed in a high-pressure unit, and then high-pressure treatment is performed. The specific steps are: first increase the pressure to a set pressure of 5.5 GPa, the pressure increase rate is 5 GPa / min, and then slowly reduce the pressure to 0 GPa after maintaining the pressure for 5 minutes, and the pressure reduction rate is 5 GPa / min;
[0060] (5) Taking out the sample after high pressure treatment in step (4), removing the metal inclusions and residual self-lubricating blocks wrapped around the outside of the sample, and obtaining WC-CBN-WS2 ceramics containing a lubricating layer.
[0061] The thickness of the ceramic lubricating layer is 60 μm. The Vickers hardness of the WC-CBN microporous ceramic is 32.5±1.1 GPa and the fracture toughness is 9.85±0.5 MPa.m. 1 / 2 ; The nanoindentation hardness of the WC-CBN-WS2 ceramic lubrication layer is 34.5±1.2GPa and the fracture toughness is 10.05±0.6MPa.m 1 / 2 The hardness and toughness of WC-based ceramics remain unchanged before and after the lubricating layer is filled.
[0062] The wear resistance of WC-CBN microporous ceramics and WC-CBN-WS2 ceramics was measured by rubbing against a cemented carbide ball (YG6) (pressure 10N, friction time 15min, rotation speed 400rpm). The wear rate of WC-CBN microporous ceramics was 148×10 -6 mm 3 / Nm, the wear rate of WC-CBN-WS2 is 19×10 -6 mm 3 / Nm, the wear resistance of WC-based ceramics after high-pressure filling of the lubricating layer is significantly improved compared with that before filling.
[0063] Comparative Example 1
[0064] The method for preparing WC-CBN-MoS2 self-lubricating ceramics comprises the following steps:
[0065] (1) CBN powder with a grain size of 5-10 μm, WC powder with a grain size of 200 nm, and MoS2 powder with a grain size of 1 μm are mixed evenly in a volume ratio of 75:20:5 to obtain a mixed powder, and pre-pressed. The pre-pressing pressure is 0.1 GPa, and the holding time is 1 s; a molded sample is obtained, and the molded sample is wrapped with a metal inclusion, and the metal inclusion is Mo;
[0066] (2) The molded sample with the metal inclusions is loaded into a high-pressure sintering unit, and then sintered at high temperature and high pressure. The specific steps are: first increase the pressure to a set pressure of 5.5 GPa at a pressure increase rate of 5 GPa / min, then increase the temperature to 1350°C, keep the temperature for 30 minutes, cool to room temperature at a cooling rate of 10°C / min, continue to keep the pressure for 5 minutes, and then slowly reduce the pressure to 0 GPa at a pressure reduction rate of 5 GPa / min;
[0067] (3) Taking out the sample after high temperature and high pressure sintering in step (2), removing the metal inclusions wrapped around the outside of the sample, and obtaining WC-CBN-MoS2 self-lubricating ceramics.
[0068] The Vickers hardness of the WC-CBN-MoS2 self-lubricating ceramic of Comparative Example 1 was measured to be 27.5±1.0GPa and the fracture toughness was 7.95±0.5MPa.m 1 / 2 ; The wear resistance of WC-CBN-MoS2 was measured by rubbing against a cemented carbide ball (YG6) (pressure 10N, friction time 15min, rotation speed 400rpm). The wear rate of WC-CBN-MoS2 was 80×10 -6 mm 3 The hardness, toughness and wear resistance of the WC-CBN-MoS2 self-lubricating ceramic prepared in Comparative Example 1 are all lower than those of the WC-based self-lubricating ceramic prepared in Examples 1-3.
[0069] The above description of the disclosed embodiments enables one skilled in the art to implement or use the present invention. Various modifications to these embodiments will be apparent to one skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the present invention. Therefore, the present invention will not be limited to the embodiments shown herein, but rather to the widest scope consistent with the principles and novel features disclosed herein.
Claims
1. A WC-based ceramic self-lubricating layer filling method driven by extreme pressure, characterized in that: The steps include: (1) CBN or diamond powder and WC polycrystalline powder are uniformly mixed in a volume ratio of (1-3):(7-9) to obtain a mixed powder, the mixed powder is pre-pressed into a shape, and then wrapped with a metal inclusion; (2) sintering the mixed powder in the metal package at high temperature and high pressure, the specific steps are: first increasing the pressure to a set pressure, then increasing the temperature, maintaining the temperature, and then slowly cooling to room temperature, and finally continuing to maintain the pressure for a period of time and then slowly reducing the pressure; (3) taking out the sample sintered in step (2), removing the metal inclusions outside the sample, obtaining a WC-based porous ceramic, and then processing it into a specified shape; (4) coating the processed WC-based porous ceramic with a layer of self-lubricating powder, and then coating it with a metal inclusion; The self-lubricating powder is a metal powder, and the metal inclusion is treated at high temperature and high pressure. The specific steps are: first increase the pressure to a set pressure, then increase the temperature to the melting point of the metal powder under the set pressure, keep the temperature, stop heating, continue to keep the pressure for a period of time, and then slowly reduce the pressure; Alternatively, the self-lubricating powder is a non-metallic powder, and the metal inclusion is treated under high pressure, specifically, the steps are: firstly increasing the pressure to a set pressure, maintaining the pressure for a period of time, and then slowly reducing the pressure; (5) Taking out the sample after being processed in step (4), removing the metal inclusions and residual self-lubricating blocks outside the sample, and obtaining a WC-based self-lubricating ceramic including a lubricating layer.
2. According to the method for filling a WC-based ceramic self-lubricating layer driven by extreme pressure in claim 1, it is characterized in that: In step (1), the grain size of the CBN or diamond powder is 0.2 to 50 μm, and the grain size of the WC powder is 0.2 to 10 μm.
3. According to the method for filling a WC-based ceramic self-lubricating layer driven by extreme pressure in claim 1, it is characterized in that: In step (2) and step (4), the pressure was set to 5.5 GPa.
4. The method for filling a WC-based ceramic self-lubricating layer under extreme pressure drive according to claim 1, characterized in that: In step (1), the self-lubricating powder is MoS2, WS2, Cu or Al powder, and the particle size of the self-lubricating powder is 10nm-10μm.
5. The method for filling a WC-based ceramic self-lubricating layer under extreme pressure drive according to claim 1, characterized in that: In step (1), the pre-pressing pressure is 0.1 GPa and the holding time is 1 s.
6. The method for filling a WC-based ceramic self-lubricating layer under extreme pressure drive according to claim 1, characterized in that: In step (2), the pressure increase rate and pressure reduction rate are 5 GPa / min, the temperature is increased to 1300-1800°C, the temperature increase rate is 100°C / min, the holding time is 2-50 minutes, the temperature reduction rate is 10°C / min, the pressure is maintained for 5 minutes and then the pressure is slowly reduced to 0 GPa.
7. The method for filling a WC-based ceramic self-lubricating layer under extreme pressure drive according to claim 1, characterized in that: The metal inclusions in step (1) and step (4) are Mo, Zr or Ta.
8. The method for filling a WC-based ceramic self-lubricating layer under extreme pressure drive according to claim 1, characterized in that: In step (4), the layer thickness of the self-lubricating powder is 0.5 mm or more.
9. The method for filling a WC-based ceramic self-lubricating layer under extreme pressure drive according to claim 1, characterized in that: In step (4), the self-lubricating powder is a metal powder, which is sintered at high temperature and high pressure, with a pressure increase rate and a pressure reduction rate of 5 GPa / min, and the temperature is increased to the melting point of the metal powder at 5.5 GPa, the temperature increase rate is 100°C / min, the holding time is 5 minutes, the heating is stopped, the pressure is maintained for 5 minutes, and then the pressure is slowly reduced to 0 GPa; Alternatively, the self-lubricating powder is a non-metallic powder, and is subjected to high pressure treatment, with a pressure increase rate and a pressure reduction rate of 5 GPa / min, and the pressure is maintained for 5 minutes and then slowly reduced to 0 GPa.
Citation Information
Patent Citations
High-strength high-wear resistance high-temperature self-lubricating composite material and preparation method thereof
CN103834866A
Self-lubricating sintered hard alloy and its production
JP1995188708A
Methods for producing ceramic-metal composites from ceramic and metal powders
WO1992016325A1